RADIATION POLYMERIZATION IN CARBON COMPOSITE MATERIALS IRRADIATED BY ELECTRONS - Aimuratov, D.B.; Kupchishin А.I.; Chen, Jie (Recent Contributions to Physics, 2008)
Influence of an ionizing irradiation on carbon composite materials at the certain dozes leads to their increase mechanical characteristics due to additional cross-linking and occurrences in polymer of cross-section bonds.